Indications for labour induction and predictors for failed induction at KMCTH - Rayamajhi, RT; Karki, C; Shrestha, N; Padhye, SM (Kathmandu University Medical Journal, 2009)
Objective: To study the incidence and indications for labour induction and study the predictors of failed induction. Materials and methods: A hospital based prospective study done over a 12 month period between 1st November 2007 to 30th October 2008. Selection criteria: Singleton pregnancies beyond 37 weeks with vertex presentation and unscarred uterus requiring induction of labour. Results: The incidence of labour induction was 19.7%. Operative delivery was 34.6% in the study group and 27.4% in those with spontaneous onset of labour. 74.07% of the induction group required operative delivery for failed induction and 25.03% for foetal distress. The predominant indication for induction was post term pregnancy (51.28%) followed by PROM (17.3%), isolated oligohydramnios (8.97%), hypertensive disorders of pregnancy (8.33%), maternal perception of decreased foetal movements (7.69%) and others. Failed induction was higher in nulliparas (41.2%) as compared to multiparas (23.7%). Failure rate was 53.8% when maternal age >30y and 28.2% in those < 30y. Women with normal BMI had a failure rate of 25.6% compared to 36% for overweight and 44.4% for obese women. 24.1% had failed induction when Bishop score was >5 and 40.8% when Bishop score was < 5. Between 38-41 weeks pregnancy failed induction occurred in 28-31% while it was higher at 41 weeks pregnancy. The best outcome was seen when the birth weight was 2500-2900g (22.5% failures) while 72.7% had failed induction when the birth weight was >3500g. The duration of induction was >24 hours in 42.6% of women and 48.2% were in the latent phase of labour when taken for caesarean section. Conclusion: Despite the proven benefit of induction of labour in selected cases, one must keep in mind its impact on increasing the rates of operative delivery. Strategies for developing practice guidelines may help to prevent unwarranted case selection and help to reduce the current high operative delivery rates. Key words: caesarean section rate, failed induction, induction of labour. doi: 10.3126/kumj.v7i1.1760 Kathmandu University Medical Journal (2009), Vol. 7, No. 1, Issue 25, 21-25